ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI EFEKTIVITAS SISTEM INFORMASI PEMERINTAH DAERAH (Studi Empiris pada Kabupaten Maluku Barat Daya) - Jeni Hanas; Theophilia Fina F Leiwakabessy (Soso-Q : Jurnal Manajemen, 2021)
Abstract:This study was aimed to examined the factors that determine the effectiveness of information systems  in  public  sector  organizations,  namely  top  management,  information  system management, user satisfaction, and the use of information systems. This study took a sample of  120  respondents  with  a  purposive  sampling  technique..  The  type  of  data  in  this  study  is primary data obtained from questionnaire answers. The data analysis used is multiple linear regression. The results showed that that information management and user satisfaction had a positive  effect  on  the  effectiveness  of  information  systems.  While  the  variables  of  top management  and  the  use  of  information  systems  had  no  effect  on  the  effectiveness  of information system.  Keywords  :  effectiveness  of  information  systems  top  management,  information  system management, user satisfaction, use of information systems.